SUCCESSION, LIVING INDIGENOUS LAW AND UBUNTU IN THE CONSTITUTIONAL COURT - GJ van Niekerk (Obiter, 2022)
In Bhe v Magistrate Khayelitsha; Shibi v Sithole; SA Human Rights Commission v President of the Republic of South Africa 2005 1 BCLR 1 (CC), the Constitutional Court by a majority declared as unconstitutional legislation regulating intestate succession in indigenous law which violated rights of equality and dignity. On the same grounds it struck down the traditional rule of male primogeniture as it applies in relation to the succession of property. In a dissenting judgement, Ngcobo J found that the rule of male primogeniture should be developed in line with the Constitution. In this article it is argued that abolition of a rule that goes to the core of indigenous law will be a theoretical exercise and will deepen the divide between living and official indigenous law. Deep legal pluralism is a reality in South Africa. Indigenous law and western law should be brought together in a relationship of equality through a process of harmonisation. The Constitution could be used as meta standard to achieve this. But a state of accord or consonance will only be realised if the key values of ubuntu are not disregarded in the process.